Tingkat Pengetahuan, Persepsi dan Sikap Pasien terhadap Kehalalan Obat Batuk Sirup yang Mengandung Alkohol di Apotek Farmarindo Banyumas - Wijayanti, Rina; Prayoga, Deden Mulya; Priyatno, Sugeng (Jurnal Sehat Mandiri, 2023)
Medicines are pharmaceutical products that play an important role in health. Medicine can reduce morbidity and improve a person's quality of life1. Alcohol is one of the substances that is forbidden by Allah SWT. One medicine that contains alcohol is cough syrup. Many patients do not know whether cough syrup is halal. Therefore, this study aims to determine and measure the level of knowledge, perceptions, and attitudes of patients regarding the halalness of cough syrup containing alcohol at the Farmarindo Banyumas Pharmacy. This research is descriptive research using a questionnaire with a sample of 80 respondents. The results of the study showed that the level of knowledge of respondents regarding the halalness of cough syrup containing alcohol was 45% in the good category. The level of perception of respondents, namely 79%, is in the good category and 21% is in the very good category. The level of respondents' attitude towards halal cough syrup containing alcohol was 74% in the good category and 26% in the very good category. It can be concluded that the level of knowledge, perceptions, and attitudes of respondents towards halal cough syrup medicine is in a good category. Muslim people are advised to ask the pharmacist first about the contents of the cough syrup they buy to find out whether it is halal.